Origin and Migration of Olfactory Cajal-Retzius Cells - Frade-Pérez, María Daniela; Miquelajáuregui, Amaya; Varela-Echavarría, Alfredo (Frontiers in Neuroanatomy, 2017)
Early telencephalic development involves the migration of diverse cells types that can be identified by specific molecular markers. Most prominent among them are Cajal-Retzius (CR) cells that emanate mainly from the cortical hem and to a lesser extent from rostrolateral, septal and caudo-medial regions. One additional territory proposed to give rise to CR cells that migrate dorsally into the neocortex lies at the ventral pallium, although contradictory results question this notion. With the use of a cell-permeable fluorescent tracer in cultured embryos, we identified novel migratory paths of putative CR cells and other populations that originate from the rostrolateral telencephalon at its olfactory region. Moreover, extensive labeling on the lateral telencephalon along its rostro-caudal extent failed to reveal a dorsally-migrating CR cell population from the ventral pallium at the stages analyzed. Hence, this work reveals a novel olfactory CR cell migration and supports the idea that the ventral pallium, where diverse types of neurons converge, does not actually generate CR cells.